2020
DOI: 10.1002/jbm.a.37063
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of adipocyte size and fat pad weight via resveratrol releasing scaffolds implanted into the epididymal adipose tissue

Abstract: Lipid overload of the adipose tissue, which can be caused by overnutrition, underlies metabolic disease. We hypothesized that increasing the energy demand of adipose tissue is a promising strategy to combat excessive lipid accumulation. Resveratrol, a natural polyphenol, activates lipid catabolism in fat tissue; however, its clinical success is hindered by poor bioavailability. Here, we implanted resveratrol releasing poly(lactide‐co‐glycolide) scaffolds into epididymal fat to overcome its poor bioavailability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 66 publications
0
3
0
1
Order By: Relevance
“…Aires et al ( 2017) studied the effects of resveratrol on CPT deficient fibroblasts and found that it was capable of modulating the expression of several microRNAs related to CPT and other enzymes related with energy metabolism such as adenosine monophosphate-activated protein kinase (AMPK). The increased expression/activity of CPT was also verified by Bastin, Lopes-Costa, and Djouadi (2011) in CPT deficient patients through an increase in the amount of CPT enzyme and its expression and fatty acid oxidation, by Murphy et al (2020) who studied the effects on implanting a resveratrol releasing scaffold on adipose tissue of mice and by K€ uhn et al (2018). Although resveratrol increased AMPK amounts/activity, this is not the only mechanism through which CPT activity and levels are restored, since using AMPK activators alone did not restore CPT to normal levels in the patients studied by Bastin, Lopes-Costa, and Djouadi (2011).…”
Section: Hyperlipidemia and Obesitymentioning
confidence: 91%
See 1 more Smart Citation
“…Aires et al ( 2017) studied the effects of resveratrol on CPT deficient fibroblasts and found that it was capable of modulating the expression of several microRNAs related to CPT and other enzymes related with energy metabolism such as adenosine monophosphate-activated protein kinase (AMPK). The increased expression/activity of CPT was also verified by Bastin, Lopes-Costa, and Djouadi (2011) in CPT deficient patients through an increase in the amount of CPT enzyme and its expression and fatty acid oxidation, by Murphy et al (2020) who studied the effects on implanting a resveratrol releasing scaffold on adipose tissue of mice and by K€ uhn et al (2018). Although resveratrol increased AMPK amounts/activity, this is not the only mechanism through which CPT activity and levels are restored, since using AMPK activators alone did not restore CPT to normal levels in the patients studied by Bastin, Lopes-Costa, and Djouadi (2011).…”
Section: Hyperlipidemia and Obesitymentioning
confidence: 91%
“…Ochiai et al (2004) were only able to find a statistically significant difference in the levels of homocysteine but not in total cholesterol, HDL or LDL, while Kozuma et al (2005) found a statistically significant difference in total cholesterol but not HDL or LDL when compared to the start of their study. There are several studies on the effects of resveratrol on CPT (Aires et al 2017;Bastin, Lopes-Costa, and Djouadi 2011;Murphy et al 2020;K€ uhn et al 2018). Aires et al ( 2017) studied the effects of resveratrol on CPT deficient fibroblasts and found that it was capable of modulating the expression of several microRNAs related to CPT and other enzymes related with energy metabolism such as adenosine monophosphate-activated protein kinase (AMPK).…”
Section: Hyperlipidemia and Obesitymentioning
confidence: 99%
“…Крізь призму жіночого здоров'я, у контексті медикаментозної корекції ожиріння та його ускладнень ресвератрол є потенційно важливим нутрієнтом з доведеною ефективністю. Препарат має доведені антиліпогенні властивості, діє на преадипоцити (індукція апоптозу, пригнічення їхньої проліферації та диференціювання, активація бурої жирової тканини) [44,45].…”
Section: ефекти ресвератролу крізь призму жіночого здоров'яunclassified
“…The infiltration of proinflammatory immune cells is associated with an increased production of proinflammatory cytokines including tumor necrosis factor α, IL-1β and IL-6. [54][55][56][57] As a result, biomaterial researchers need to identify the extent of adipose tissue deposition within, and around degrading biomaterials for specific applications [57][58][59][60] and the role this adipose tissue plays in final tissue or organ function.…”
Section: Introductionmentioning
confidence: 99%